Kewenangan Pemerintah Di Bidang Kepemudaan Dalam Rangka Mendukung Pembangunan Nasional Melalui Organisasi Kepemudaan - Siagian, Parulian Hasiholan; Mau, Hedwig Adianto; Candra, Mardi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Youth has a very important position in the history of the struggle for Indonesian independence. Youth development is Indonesia's strategic agenda in order to prepare future generations who are strong and able to play a role in the development of the nation as a whole. In the present, youth are expected to continue to be able to fulfill independence in order to support national development. Seeing the very high potential of youth, the Government then saw the need to formulate special policies related to youth development. The research method in this writing is qualitative. The type of research in this research is using normative juridical law research. The purpose of the establishment of the Youth Law which provides specificity for the implementation of affairs in the field of youth cannot be carried out optimally so that it also has an impact on the Government's efforts in implementing youth development which is expected to support national development.Keywords: Authority; Youth; National development AbstrakPemuda memiliki kedudukan yang sangat penting dalam sejarah perjuangan kemerdekaan Indonesia. Pembangunan pemuda merupakan agenda strategis Indonesia dalam rangka mempersiapkan generasi masa depan yang tangguh dan mampu berperan dalam pembangunan bangsa secara keseluruhan. Di masa sekarang, pemuda diharapkan terus dapat mengisi kemerdekaan guna mendukung pembangunan nasional. Melihat potensi kaum muda yang sangat tinggi, Pemerintah kemudian memandang perlu menyusun kebijakan khusus terkait dengan pembangunan kepemudaan. Metode penelitian dalam penulisan ini adalah kualitatif, jenis Penelitian dalam penelitian ini yaitu menggunakan penelitian hukum yuridis normative. Tujuan pembentukan Undang-Undang Kepemudaan yang memberikan kekhususan penyelenggaraan urusan dibidang kepemudaan tidak dapat dilaksanakan dengan maksimal sehingga berdampak pula terhadap upaya Pemerintah dalam melaksanakan pembangunan kepemudaan yang diharapkan dapat mendukung pembangunan nasional.Kata Kunci: Kewenangan; Kepemudaan; Pembangunan Nasional